PENGARUH KUALITAS SISTEM, KUALITAS INFORMASI, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PENGGUNA DAN DAMPAKNYA TERHADAP KEPERCAYAAN (TRUST) PENGGUNA E-KATALOG DI PROVINSI DKI JAKARTA - Kriston Panggabean; Aty Herawati, R; Dwi Sunu Kanto (PT. Hasba Edukasi Mandiri, 2025)
Indonesia’s government e-catalog procurement system has emerged as a key innovation in enhancing efficiency, transparency, and competitiveness in public procurement. However, the determinants of vendor trust in this platform remain insufficiently examined, particularly from the supplier’s perspective. This study aims to analyze the influence of system quality, information quality, and service quality on user satisfaction, and its subsequent effect on trust among e-catalog vendors in DKI Jakarta. A quantitative associative research design was applied, involving 98 respondents representing registered vendors. Data were collected via a structured Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM–PLS). The findings indicate that system quality does not significantly affect user satisfaction, while both information quality and service quality exert positive and significant effects. Moreover, user satisfaction demonstrates a strong and significant impact on trust in the e-catalog system. These results reinforce the applicability of the DeLone and McLean Information Systems Success Model in the e-government procurement context, highlighting that timely, accurate, and relevant information, combined with responsive and reliable service, are critical for fostering vendor trust. Policy implications emphasize the need to strengthen information management and service responsiveness to enhance vendor engagement, while future research could explore additional constructs or regional comparisons to broaden understanding.